Assessing amino acid uptake and metabolism in mammary glands of lactating dairy cows intravenously infused with methionine, lysine, and histidine or with leucine and isoleucine - Huang, X.; Yoder, P. S.; Teixeira, I. A. M. A. [UNESP]; Hanigan, M. D. (Elsevier B.V., 2021)
The objective of this study was to evaluate the effect of jugular infusions of 2 groups of AA on essential AA (EAA) transport and metabolism by mammary glands. Four Holstein cows in second lactation (66 +/- 10 d in milk) were used in 4 x 4 Latin square design with a 2 x 2 factorial arrangement of treatments. Treatments were jugular infusions of saline; Met, Lys, and His (MKH); Ile and Leu (IL); or MKH plus IL (MKH+IL). Each period consisted of 8 d of no infusion followed by 8 d of jugular vein infusion of the treatment solutions. Amino acids were infused at rates of 21 g of Met, 38 g of Lys, 20 g of His, 50 g of Leu, and 22 g of Ile per day. Cows were fed a basal diet consisting of 15.2% crude protein with adequate rumen degradable protein but 15% deficient in MP based on estimates by Cornell Net Carbohydrate and Protein System (v6.5). On the last day of each period, C-13-AA derived from algae was infused into the jugular vein over 6 h, and blood and milk samples were collected before, during, and after infusion. Plasma and milk samples were analyzed for AA isotopic enrichment, and a mammary compartmental model was fitted to the data to derive bidirectional transport and metabolism rates for individual EAA. Influx of Leu increased with IL, whereas influx of other EAA was not different among treatments. Cellular efflux of Met and Lys to venous plasma represented 12 to 34% of influx, whereas cellular efflux of Phe and BCAA represented 29 to 59% of influx. Increased efflux/influx ratios of Ile and Leu with IL but not Met and Lys with MKH demonstrated that increased Ile and Leu influx was mostly returned to plasma resulting in no change in net uptake or efficiency. The isotope results showed that mammary net uptake of Lys and Ile increased during MKH infusion. Net uptake of Met increased with MKH but only in the absence of IL. Catabolism of Lys and Met only increased with MKH alone, resulting in decreased efficiency for milk protein, which demonstrated that Ile and Leu infusion can spare Lys and Met for milk protein synthesis. Total AA uptake to milk output was not different from 1, implying the catabolized Met and Lys contributed nitrogen to nonessential AA. Overall, EAA uptake and metabolism in mammary glands of dairy cows varied across individual EAA and responded differently to respective AA supplements. In addition, uptake, retention, and end use of AA by mammary tissue is variable and dependent on the mix of AA provided. This variability, depending on the mix of AA absorbed, will change the efficiency of utilization of individual AA at the mammary gland level and consequently the whole-body level. Thus, it is inaccurate to use a fixed, constant efficiency within and across AA to represent tissue activity.
Keywords: essential amino acids; stable isotope; metabolism; mammary glands